Intensive Physiotherapy Interventions in Speedy Recovery of Sub-acute Stroke: A Case Series - Adhikari, Shambhu P.; Maharjan, Riju; Jakibanjar, Redisha; Balla, Anushree; Shrestha, Manisha; Shalike, Narendra; Nepal, Govinda M. (Journal of Lumbini Medical College, 2020)
Introduction: Intensive physiotherapy interventions have shown good recovery in stroke if applied to stable patients who can tolerate it. Influence of enriched environment on intensive physiotherapy interventions after acute care has not been studied in low-resource contexts, and therefore, we reported outcome of the interventions in multiple cases with stroke in Nepalese context and cultural background. Case reports: Three patients in sub-acute stage of stroke were admitted in intensive physiotherapy treatment unit where the environment was therapeutically enriched. The therapist-administered interventions were intensive for each domain of impairment and activity limitations, every day for six days a week. Patients were trained to carry out caregiver-assisted practice or self-practice in enriched environment. Training demonstrated visible and measurable outcome in all cases. Conclusion: Intensive physiotherapy interventions in an enriched environment promoted good recovery in short period in stroke. The interventions applied, and the principles adopted were based on the established evidence, and therefore findings of this study may support for its feasibility and applicability.